Lifetime musculoskeletal symptoms and injuries among former elite male athletes - Raty, H. P.; Kujala, U. M.; Videman, T.; Impivaara, O.; Crites Battie, M.; Sarna, S. (International Journal of Sports Medicine, 1997)
We studied the lifetime occurrence of musculoskeletal symptoms in former elite male athletes: 29 weight-lifters, 31 soccer players, 28 long-distance runners, and 29 shooters, 45-68 years of age. The proportion of subjects with monthly back pain during the past year was smaller among runners than among the other athletes, although not statistically significant. Monthly back pain was more common in weight-lifters with lifetime training hours above the median as compared with those below the median. The average intensity of the worst back pain during the past year was clearly higher in weight-lifters and soccer players, than in runners and shooters. Knee pain at least once a month during the past year was reported by 52% (CI 33-70%) of the soccer players, 31% (CI 15-51%) of the weight lifters, 21% (CI 8-41 %) of the runners, and 17% (CI 6-36%) of the shooters (p = 0.019). Soccer players had the highest number of sports-related knee injuries (p < 0.0001). Past knee injuries were associated with knee pain in later adulthood (p = 0.048). More runners reported having had hip pain episodes during their lifetime than other athletes, but no differences were found in the occurrence of hip pain during the past year. In conclusion, compared with shooters, athletes formerly exposed to heavy exercise did not report more frequent back pain during the past year, whereas a high intensity of back pain was typical of soccer players and weight-lifters. A predisposition to knee injuries in soccer players appears to increase the risk of future knee pain. Similarly, knee pain later in life seems to be more common in weight-lifters than in runners and shooters. Long-distance runners, on the other hand, are prone to an increased lifetime risk of hip pain.